Imam Al-Ghazali's educational thought and its relevance to contemporary Islamic education literature review on scopus indexed articles - Onilivia, Viva Fadma; Noptario; Maragustam; Putri, Nadya Syafira (TAWAZUN: Jurnal Pendidikan Islam, 2025)
Al-Ghazali is a famous Islamic philosopher scholar, nicknamed Imam Al-Ghazali because of his views and deep knowledge of various religious sciences is as a blasphemy of Islam. According to Imam Al Ghazali, Islamic education is a process that will make humans as brilliant beings so that they will get happiness while living in the world and in the hereafter by staying closer to the creator, namely Allah Almighty through the knowledge that has been obtained through the process of education. Education today is relevant and in line with the concept of Imam Al-Gahzali regarding education which can be known from various components of education, both from educational objectives, curriculum, methods used in the educational process, educators and students themselves. This article traces research on the thought of Imam Al-Ghazali in the journal indexed by Scopus. The reason for choosing the reference limit is only in Scopus indexed journals so that the data obtained can be more reliable because it is published in reputable international journals. The urgency of this discussion is for science in the treasures of Islamic education, namely the relevance between contemporary Islamic education today according to Imam Al-Ghazali and educational thinking. Abstrak Al-Ghazali adalah seorang ulama filsuf Islam yang terkenal, dijuluki Imam Al-Ghazali karena pandangan dan pengetahuannya yang mendalam tentang berbagai ilmu agama adalah sebagai seorang mujtahid. Menurut Imam Al Ghazali, pendidikan Islam adalah sebuah proses yang akan menjadikan manusia sebagai makhluk yang cemerlang sehingga akan mendapatkan kebahagiaan selama hidup di dunia dan di akhirat dengan cara mendekatkan diri kepada sang pencipta, yaitu Allah SWT melalui ilmu yang telah didapatkan melalui proses pendidikan. Pendidikan saat ini relevan dan sejalan dengan konsep Imam Al-Gahzali mengenai pendidikan yang dapat diketahui dari berbagai komponen pendidikan, baik dari tujuan pendidikan, kurikulum, metode yang digunakan dalam proses pendidikan, pendidik dan peserta didik itu sendiri. Artikel ini menelusuri penelitian mengenai pemikiran Imam Al-Ghazali dalam jurnal yang terindeks Scopus. Alasan pemilihan batasan referensi hanya pada jurnal terindeks Scopus agar data yang diperoleh dapat lebih terpercaya karena dipublikasikan pada jurnal internasional bereputasi. Urgensi dari pembahasan ini adalah untuk keilmuan dalam khazanah pendidikan Islam, yaitu relevansi antara pendidikan Islam kontemporer saat ini menurut Imam Al-Ghazali dengan pemikiran pendidikan.